2018
DOI: 10.1097/gox.0000000000001711
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Morbidity in Patients after Head and Neck Reconstruction with the Pedicled Supraclavicular Island Flap

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…After assessment for distal viability, the flap must then be adapted to the defect. In the case of defects within the oral cavity, oropharynx, or hypopharynx, the proximal portion of the flap is de-epithelialized and can be tunneled through the neck or mediastinum to the desired area 5,6,11 . The flap may be inset in a corkscrew fashion to achieve greater diameter in pharyngeal reconstruction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After assessment for distal viability, the flap must then be adapted to the defect. In the case of defects within the oral cavity, oropharynx, or hypopharynx, the proximal portion of the flap is de-epithelialized and can be tunneled through the neck or mediastinum to the desired area 5,6,11 . The flap may be inset in a corkscrew fashion to achieve greater diameter in pharyngeal reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…The success rate of SCF reconstructions, as reported in the literature, is approximately 96% (complete flap failure 3.4%), with reports of minor complications at 24.6%. 11 Selection of the proper reconstructive technique can prove difficult, and ultimately an individually tailored approach should be taken, which accounts for patient sex, defect size, desired flap thickness, prior radiation, comorbidities, ability to endure longer general anesthesia, donor site morbidity, vessel availability and quality, skin color, and more. Particularly in female patients, the SCF allows reconstruction of the head and neck without disruption of breast appearance.…”
Section: Flap Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some degree of limitation in range of motion in abduction and external rotation was seen in most patients, although strength was preserved. Spiegel et al 43 also used a patient-reported survey and found no differences in pain, range of motion, and extremity strength between the SAI flap side and nonoperated side. Referred sensation to the shoulder, especially in patients with mucosal reconstruction during oral intake, was observed in a number of patients.…”
Section: Complicationsmentioning
confidence: 99%